An evaluation of horizontal equity in surgical care for gallstone disease in a Caribbean country - Avidesh Haresh Mahabir; Solange C K Ramkissoon; Dexter A Thomas; Shamir O Cawich; Vijay Naraynsingh; Giovanni Dapri (Current Medicine Research and Practice, 2021)
Background: The aim of this study was to identify social injustice by evaluating horizontal equity (allocation of similar resources to patients with the same clinical needs) in surgical care for gallstone disease in a Caribbean Country. Methods: We compared access to laparoscopic cholecystectomy (LC) for gallstone disease between a fee-for-service (private) and a government-funded (public) health-care system between 1st January and 31st August, 2018. We defined a prolonged waiting time as an interval of >90 days between the index diagnosis and LC. The data were examined using SPSS v23. Results: Ninety-nine patients underwent LC in public (60) or private (39) hospitals. There was a significantly longer mean waiting time in public hospitals (336.4 ± 647.9 days vs. 20.2 ± 25.5 days; P 0.002) and significantly more hospital readmissions while awaiting LC (72% vs. 0%). In the public hospital system, fewer patients had ambulatory operations (8.4% vs. 51.3%; P < 0.00001) and the mean duration of operation was longer (2.4 ± 0.88 vs. 0.92 ± 0.34 h; P < 0.0001). There were no differences in morbidity or mortality between the health-care systems. Thirty-eight patients had prolonged waiting times due to: long pre-existent waiting lists (13), consumables out of stock (10), equipment malfunction (6), patient request (3), pre-operative Endoscopic retrograde cholangiopancreatography (2), unspecified (2) and anaesthetic optimisation (1). One patient in the private hospital had a delay >90 days while awaiting insurance pre-authorisation. Conclusion: Horizontal inequity exists between the health-care systems. There is room for improvement through increased accountability for administrators, better resource allocation, proper equipment maintenance schedules and efforts to reduce waiting lists.